Using Agents & Artifacts to Access the Semantic Web A Recommender System Case Study - Bonson, Jéssica Pauli de C.; Santos, Elder Rizzon (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2014)
In this paper we integrate the access of agents to the Semantic Web by means of the Agents & Artifacts model, using the Cartago framework. Our case study is a recommender system to define metadata of a Learning Object according to a metadata standard. The agents are able to provide recommendations by querying the DBPedia through artifacts. The contribution of our work is to develop a prototype integrating MAS to the Semantic Web using artifacts.